PONDOK PESANTREN IBNU TAIMIYAH SINGKAWANG - Uray Zulfaa Nurul Farhanah; Syaiful Muazir; Valentinus Pebriano (JMARS: Jurnal Mosaik Arsitektur, 2022)
Pesantren is an Islamic Education and Broadcasting Institution, Islamic boarding schools also teach general knowledge, organize, socialize and so on. as a provision to navigate life in the world. In Indonesia, many Islamic boarding schools have been established, generally having student dormitories, places of worship, schools, residences for clerics or clerics, kitchens, and others needed for housing, worship, and education. Ibnu Taimiyah Islamic Boarding School is located in Singkawang City, precisely on Jl. Education, Sedau, Singkawang Sel.. Singkawang City, West Kalimantan 79163. The location of this Islamic boarding school is located in a tourist area. This pesantren has been established since 1991 by KH Ahmad Hambali Lc. However, this pesantren is not growing fast because of the factors that become the weakness of the pesantren, one of the weaknesses of the architectural field is the lack of adequate facilities. The design of this final project aims to redesign the Ibnu Taimiyah Islamic Boarding School by taking into account the environment and its functions, and the suitability of geographical potential. It is hoped that the results of this redesign can play a role in the establishment of the economic independence of the Ibn Taimiyah Islamic Boarding School so that it is known to the public in addition to being an added value for the Ibn Taimiyah Islamic Boarding School so that people are interested in studying at the Ibn Taimiyah Islamic Boarding School Singkawang.